2015
DOI: 10.1111/ecin.12230
|View full text |Cite
|
Sign up to set email alerts
|

Does Bankruptcy Law Affect Business Turnover? Evidence From New and Existing Business

Abstract: This study examines how differences in state bankruptcy laws, specifically the homestead exemption, affect business turnover by studying both new and existing businesses. We focus on areas just near state boundaries to control for unobserved local attributes to better isolate the effect of more wealth protection. We find that an increase in the homestead exemption attracts new businesses but also has a positive impact on existing businesses, suggesting that asset protection through bankruptcy law encourages su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The authors look at how the program affected firm deaths, and find no evidence that the program was simply creating more business turnover. This is also consistent with the work ofRohlin and Ross (2016), which considers the effect of bankruptcy law on business turnover and found that if anything more generous bankruptcy exemptions increase the number of existing businesses, likely because the more generous protections in bankruptcy encourage entrepreneurs to incur the risk of opening their own business Rohlin, Rosenthal, and Ross (2014). further consider how differences in policy may cause sorting of different types of business activity across state boundaries.3 In their research, the authors look at how differences in state tax policy affect the relative sorting of business activity across state lines.…”
supporting
confidence: 93%
“…The authors look at how the program affected firm deaths, and find no evidence that the program was simply creating more business turnover. This is also consistent with the work ofRohlin and Ross (2016), which considers the effect of bankruptcy law on business turnover and found that if anything more generous bankruptcy exemptions increase the number of existing businesses, likely because the more generous protections in bankruptcy encourage entrepreneurs to incur the risk of opening their own business Rohlin, Rosenthal, and Ross (2014). further consider how differences in policy may cause sorting of different types of business activity across state boundaries.3 In their research, the authors look at how differences in state tax policy affect the relative sorting of business activity across state lines.…”
supporting
confidence: 93%
“…There has been an extensive discussion on how various factors, including tax policy and bankruptcy procedures, affect entrepreneurial activity (Borchers, Deskins, and Ross 2016;Bruce 2002;Bruce and Deskins 2012;Fan and White 2003;Georgellis and Wall 2006;Rohlin, Rosenthal, and Ross 2014;Rohlin and Ross 2016). However, the most frequently cited obstacle to becoming an entrepreneur is the large amount of financing needed to start a business.…”
Section: Existing Researchmentioning
confidence: 99%
“…They empirically confirm this using household level data. Rohlin and Ross (2015) uses the discontinuity in exemption levels across state borders and find that states with higher exemption levels attract more new businesses and also have positive effects on existing businesses. Similarly, I will find strong evidence that more generous homestead exemption increases small business births in MSA's.…”
mentioning
confidence: 99%